Challenges and Opportunities for Promoting Entrepreneurship and Youth Employment in Lalbandi Municipality, Nepal - Chaudhary, Birendra (Janajyoti Journal, 2025)
Youth unemployment poses a critical socio-economic challenge in Nepal, with semi-urban municipalities like Lalbandi in Madhesh Province facing acute difficulties. Promoting entrepreneurship is increasingly recognized as a viable strategy for enhancing youth employment, yet several contextual barriers persist. This study aims to identify the primary challenges and opportunities associated with fostering entrepreneurship as a means to address youth unemployment in Lalbandi Municipality, with specific attention to gender, institutional, and socio-cultural dynamics. A mixed-methods approach was employed, integrating quantitative data from structured questionnaires administered to 75 youth respondents and qualitative insights from interviews and focus group discussions involving 20 key stakeholders. Analyses focused on employment status, access to resources and support programs, socio-cultural perceptions, and institutional capacity. Quantitative findings indicate that a significant proportion of Lalbandi’s youth are either unemployed or engaged in informal employment, lacking access to financial services, vocational training, and government-led entrepreneurship schemes. Qualitative data highlight prevailing cultural barriers—especially for female youth—institutional limitations in program implementation, and low trust in public agencies. Nevertheless, promising opportunities are evident, including burgeoning digital entrepreneurship, agri-business potential, and mechanisms of cooperative-driven support. Many youth expressed readiness to engage in entrepreneurial activities, contingent upon improved access to resources and enabling support systems. The study underscores the necessity for locally tailored, youth-centered policy responses to promote entrepreneurship and employment. Key recommendations include expanding collateral-free lending, introducing practical and market-oriented vocational training, enhancing institutional outreach and responsiveness, fostering gender-sensitive environments, and integrating digital tools. These interventions could facilitate the unleashing of entrepreneurial potential among Lalbandi’s youth, thereby contributing to sustainable, community-driven development.